Creative Marketing and Its Role in Raising Customer Value - Al Khazraje, Mohammed Edan; Hussein, Entisar Azeez; Sideeq, Suhaer Shakir (International Review of Management and Marketing, 2026)
The research examines the correlation and impact of creative marketing on customer value, emphasizing its role in enhancing value. The core issue focuses on the extent to which Al-Kafeel Food Products Company utilizes creative marketing to achieve this goal. The research sample consisted of (226) respondents from Al-Kafeel Food Products Company customers who were randomly selected. An electronic questionnaire was used for data collection, published on social networking sites (Facebook, Instagram). The descriptive analytical approach was employed to analyze the responses, using SPSS V26 and SmartPLS software to derive the results. The research concluded that there is an impact and correlation between creative marketing and customer value. Creative marketing plays an important role in distinguishing companies from competitors by providing unique offers that add value to customers. This distinction helps attract customers’ attention and increase their interest in the products or services provided.